Evaluation of the implementation outcomes of the framework and strategy for disability and rehabilitation for South Africa: a mixed-methods study protocol - Kout, Naeema AR Hussein El; Pilusa, Sonti; Damons, Natalie Benjamin (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: The prevalence of disability is increasing. The rights of persons with disabilities have not been upheld and health policy is a tool to actualise these rights. The Framework and Strategy for Disability and Rehabilitation (FSDR) for South Africa (2015-2022) has expired but the implementation process has not been evaluated to inform future disability policy implementation. Objectives: To evaluate the perceptions of the implementation of the FSDR to develop implementation strategies. Method: An explanatory mixed methods study comprising of a document review, semi-structured interviews and focus group discussions with stakeholders involved in the implementation process of the FSDR in Gauteng province, will be employed. The document review and interview transcript analysis will utilise initially inductive thematic analysis (Alhojailen), followed by deductive analysis using established implementation science frameworks. Data will be triangulated from semi-structured interviews and focus group discussions to develop implementation strategies for future disability policy. Clinical implications: This study will contribute to the field of policy analysis, as well as improving the implementation of future disability policy in South Africa to protect the rights of persons with disabilities. The study findings may also be used as a tool for advocacy to improve rehabilitation service provision in South Africa. International Journal of Human and Health Sciences Vol. 07 No. 04 Oct’23 Page: 277-285